THE INFLUENCE OF SERVICE QUALITY, PRODUCT QUALITY, AND STORE ATMOSPHERE ON THE DECISION TO VISIT PADAGRAHA COFFE &; RESTO IN LHOKSEUMAWE - Nazila Firza; Agustinawati; Nurainun; T. Edyansyah (RADJA PUBLIKA, 2024)
The purpose of this study is to determine and analyze the influence of service quality, product quality and store atmosphere on the decision to visit Graha Coffee & Resto in Lhokseumawe. This type of research uses associative research types and sampling techniques in this study using purposive sampling techniques with a total of 96 respondents. Primary data in this study were taken by distribution of questionnaires, and secondary data obtained from journals and books. The data analysis techniques used are descriptive analysis methods and multiple linear regression analysis, classical assumption tests, instrument tests (validity and reliability), hypothesis testing (t-test and F-test) using the SPSS program version 21.0. The test results showed that: 1) simultaneously influenced the decision to visit Graha Coffee & Resto in Lhokseumawe.The test results obtained a Fcalculate value of 11.346 with a significance of 0.007>0.05. thus the results of hypothesis testing on the F (simultaneous) test show the influence of service quality variables, product quality and store atmosphere together on the decision to visit. 2) paarsial influence on the decision to visit Graha Coffee & Resto in Lhokseumawe. The test results partially show that service quality (X1) has a regression coefficient of 0.098 then H1 is accepted, product quality (X2) has a regression coefficient of 0.005 then H2 is accepted, and store atmosphere (X3) has a regression coefficient of 0.048 then H3 is accepted. Of the three variables, it has a significance value of <0.05, thus the results of the t test (partial) show a positive and significant influence of the variables of service quality (X1), product quality (X2) and store atmosphere (X3) on the decision to visit (Y) at Graha Coffee & Resto in Lhokseumawe.